Distributed object-based software environment for urban system integrated simulation under urban-scale hazard?Part II Application. - Serror, M. Hassanien (Earthquake engineering & structural dynamics.)
A software prototype of a simulation service software environment, called DOSE (distributed object-based software environment), is developed to realize the integrated simulation of an urban system under the risk of urban-scale hazards such as earthquakes. DOSE infrastructure is built on three basic building blocks, namely: modularity, scalability, and interoperability. In this paper, the application of DOSE to real-world urban systems is described in order to provide an evidence for DOSE modularity and scalability. An overview of DOSE is presented and then followed by a beverage application to simulate earthquake hazard in an urban system. The urban system is developed for the city of Kobe (Kobe district) with dimensions of 700 × 500 (m) and Bunkyo ward (Tokyo district) with dimensions of 800 × 600 (m) where DOSE simulation participants are identified for each district. The effectiveness of data exchange among different participants through a distributed service exchange network is described as an evidence for DOSE modularity that facilitates the integration process. On the other hand, the effectiveness of processing time when applying the simulation to different urban system sizes and/or using different third-party applications is described as an evidence for DOSE scalability. The details of the underlying infrastructure of DOSE are beyond the scope of this paper and are presented in an accompanying paper work.